Tinjauan Pustaka: Klasifikasi dan Tatalaksana Trauma Aurikuler - Aurora Awindya Nareswari; Putu Ristyaning Ayu Sangging; Rani Himayani (Medula, 2023)
The auricle is the outermost part of the ear so it is very susceptible to injury. Injury or trauma to the auricles can occur intentionally or unintentionally, with the most common causes being accidents, bullet injuries, frostbites, burns, animal bites, and others. Some types of activities have a high risk of experiencing this type of trauma such as wrestling, boxing, and soccer. The most common types of trauma to the auricle are abrasions, lacerations, avulsions, and auricular hematomas. Auricular lacerations can be caused by a hard blow with a blunt object, an incision from a sharp object such as a knife, an accident, and others. Meanwhile, an auricular hematoma is an abnormal condition due to trauma to the auricle which causes a buildup of blood between the cartilage and perichondrium. If not treated or treated late, this condition can lead to fibrosis of the cartilage and the formation of neocartilage, then ends with cauliflower ear which can cause drastic changes in the auricles. Therefore, the diagnosis and management of auricular trauma must be carried out appropriately and adequately so as not to cause discomfort to the patient due to its effect on the patient's appearance.